Analysis of determinants of the inflow of foreign direct investment to Poland. Part II - research results - Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
This study contains an analysis of the main determinants of the inflow of foreign direct investment to Poland. This article is devoted to the analysis of the main motives determining the inflow of foreign direct investment to Poland. It is the second part of the series and presents the scale and dynamics of FDI inflow to Poland between 2010 and 2018, as well as the results of own research carried out using structural equation modeling.
Keywords: foreign direct investment; FDI in Poland; structural equation modeling; SEM; bezpośrednie inwestycje zagraniczne; BIZ w Polsce; modelowanie równań strukturalnych